Contemporary Trends in Dental Caries Management: A Systematic Review - Mariam Yhia Ali Almthami; Khlood Hamed Mohammed Alshamrani; Hanan Hassan Assiri; Layal Abdullah Abdulhafith Aljaddawi; Dunya Ahmed Mohammed Alghamdi; Ghadah Ayidh Sultan Albaqami; Asma Alassaf (International Journal of Medical Toxicology and Legal Medicine, 2025)
Dental caries remains one of the most prevalent chronic diseases worldwide, affecting individuals across all age groups and socioeconomic backgrounds. Traditional restorative approaches, while effective in managing lesions, have not significantly reduced global incidence rates, highlighting the need for a paradigm shift in caries management. This systematic review explores contemporary trends in dental caries management, drawing from recent literature published between 2015 and 2025. The review identifies a clear movement toward minimally invasive dentistry, emphasizing early detection, risk assessment, and preventive strategies. Innovations such as silver diamine fluoride, remineralization therapies, and non-invasive treatment modalities have demonstrated clinical efficacy, particularly in pediatric and underserved populations. Additionally, the integration of artificial intelligence, digital diagnostic tools, and teledentistry is reshaping diagnostic accuracy and access to care. Patient-centered models like CAMBRA further support individualized treatment planning based on caries risk. Despite promising advances, challenges persist in terms of clinical implementation, cost-effectiveness, and long-term outcomes. This review highlights the importance of adopting evidence-based, technology-enhanced, and patient-specific strategies to combat the burden of dental caries and underscores the need for ongoing research in diverse populations and settings.